An Assessment of Undergraduate learning outcomes in service-learning engagement: A Phenomenological Study in a Malaysian Institution of Higher Learning. - Shanmugam, Karthiyani (2018)
Service-learning is a teaching and learning strategy that integrates community service with instruction to instill civic attitude and enrich students’ learning experience. The Malaysian Education Blueprint 2015-2025 (Higher Education) states service-learning as one of the ways to develop students’ 21st century skills. However, there is not much research done on service-learning in the Malaysian context. This study is prompted by views that Malaysians in general lack civic attitude and Malaysian graduates lack academic skills. Therefore, the study aims to assess undergraduate learning outcomes in service-learning engagement based on a case study in a Malaysian higher learning institution and find out whether service-learning is able to develop civic attitude and academic skills. This research is founded on Kolb’s Experiential Learning Theory and Mezirow’s Transformational Learning Theory. It is a phenomenological study using qualitative research methodology. Data was collected for textual analysis from students and lecturers through semi-structured interviews of students, individual reflective journal of students, group reflective report of students, semi-structured interview of lecturers, reflective journal of lecturers and observation of students. Students were asked to describe their lived experience of participating in service-learning project. The participants of this study were year one and year two diploma students from various disciplines taking a compulsory general studies course, namely Civic Consciousness and Volunteerism in a private higher learning institution in Malaysia and the lecturers who taught them. The course requires students to carry out a group project, which benefits the community within a semester. The service-learning projects carried out by the students were categorised into three themes, i.e. environment, filial piety and underprivileged children. The findings show that students experienced various civic, academic, and personal and social outcomes, including awareness of community issues, sympathy, compassion and respect for the affected community, the intention to be involved in charity activities in the future, teamwork skills, communication skills, leadership skills, thinking and problem-solving skills, planning and organising skills, sense of achievement, happiness, gratefulness, and realisation of own weaknesses. Most of the lived experiences shared by students were positive. The findings suggest that service-learning has the ability to develop students’ civic attitude and academic skills.